Design approaches for critical embedded systems: A systematic mapping study - Feitosa, Daniel; Ampatzoglou, Apostolos; Avgeriou, Paris; Affonso, Frank J. [UNESP]; Andrade, Hugo; Felizardo, Katia R.; Nakagawa, Elisa Y. (Springer Nature, 2018)
Critical Embedded Systems (CES) are systems in which failures are potentially catastrophic and, therefore, hard constraints are imposed on them. In the last years the amount of software accommodated within CES has considerably changed. For example, in smart cars the amount of software has grown about 100 times compared to previous years. This change means that software design for these systems is also bounded to hard constraints (e.g., high security and performance). Along the evolution of CES, the approaches for designing them are also changing rapidly, so as to fit the specialized needs of CES. Thus, a broad understanding of such approaches is missing. Therefore, this study aims to establish a fair overview on CESs design approaches. For that, we conducted a Systematic Mapping Study (SMS), in which we collected 1,673 papers from five digital libraries, filtered 269 primary studies, and analyzed five facets: design approaches, applications domains, critical quality attributes, tools, and type of evidence. Our findings show that the body of knowledge is vast and overlaps with other types of systems (e.g., real-time or cyber-physical systems). In addition, we have observed that some critical quality attributes are common among various application domains, as well as approaches and tools are oftentimes generic to CES.
Keywords: Critical embedded system; Design; Systematic mapping study